Successful Intravitreal Injection of Ranibizumab for Age-Related Macular Degeneration (AMD) in Young Adults: A Case Report - Adnani, Basyar; Sumarta, Norma Hanifah; Famuji, Siti Roziah Ria; Khotimah, Alif Raudhah Husnul; Halim, Putri Aulawiya Rosyida; Hasan, Yuliono Trika Nur; Hutasoit, Lina Puspita (Journal of Islamic Medicine, 2024)
Background:  Age Related Macular Degeneration (AMD) is a chronic condition that specifically affects the central retina and is widespread in developed nations. The hypothesis suggests that as the population ages, the occurrence and impact of AMD will rise due to the significant risk factor of being over 55 years old, which is most prevalent among the elderly. Bevacizumab, ranibizumab, and aflibercept have established themselves as the gold standard of therapy. Case Report:  We present the case of a middle-aged man with age-related macular degeneration (AMD) and no concomitant diseases who showed remarkable improvement after intravitreal injection with patizra (ranibizumab). A 44-year-old Asian man was administered Patizra injections for three consecutive months after developing age-related macular degeneration. After intravitreal injection of ranibizumab, this patient's health markedly improved, as seen by a reduction in subretinal fluid. Conclusion:  The intravitreal injection of ranibizumab has demonstrated efficacy in the treatment of age-related macular degeneration in middle-aged adults.